Memory, space, and identity: streets as an element of local identity enhancement in São José dos Campos (São Paulo – Brazil): Memory, space, and identity: streets as an element of local identity enhancement in São José dos Campos (São Paulo – Brazil) (Revista de História da UEG (REVHIST), 2025)
The article discusses the formation and appreciation of local identities in the municipality of São José dos Campos through changes in street names. In 1913, a resolution signed by the mayor of the municipality changed the names of public roads from important civic dates in Brazilian history to names of figures emblematic to the history of the municipality. As memory, space, and identity are interconnected concepts, the purpose of this research is to demonstrate how this resolution culminated in the enhancement of local urban memory through toponymy, a science that studies the names of places. In addition to analyzing Resolution No. 13, the use of toponymy and Historical GIS was necessary to better understand the urban space of São José dos Campos during that period. The results demonstrated the respective appreciation of the public authorities for these figures of relevance to local history.Keywords: memory; space; identity; urban history; streets.
Keywords: Memory; Space; Identity; Urban History; Streets